Nasal leprosy: an ancient disease not to be forgotten - Andrew CGJ; Chong HS (International Journal of Medical Research and Review, 2016)
We are reporting a case of a gentleman referred to a tertiary care center for epistaxis associated with maggots in the nose and was found to have a nasal septal perforation. He underwent investigations with histopathologic analysis and skin slit smear to obtain a diagnosis. The patient received multidisciplinary management including endoscopic removal of the maggots and biopsies obtained from both the nasal septum and leg ulcers and subsequently anti leprosy medication.